2019
DOI: 10.3389/fmech.2019.00050
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Semi-empirical Flame Models for Spreading Chaparral Crown Fire

Abstract: Flame geometry plays a key role in shaping fire behavior as it can influence flame spread, radiative heat transfer and fire intensity. For wildland fire, thorough characterizations of flame geometry can help advance the derivation of comprehensive models of wildfire behavior. Within the fire community, a classical flame modeling approach has been to develop semi-empirical models. Many of these models have been derived for surface fuels or for pool fire configurations. However, few have sought to model flame be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Personal communication, John Maitland, Chief, Forestry Branch, USAG Ft. Jackson to David Weise, 2015. While Fire 2022, 5, 118 sparkleberry was the focus of the present study, Wenk et al [58] found similar results in another prescribed fire study in the Carolina sandhills in longleaf stands where turkey oak (Quercus laevis) was the dominant understory woody plant [59][60][61][62]. It is well-established that natural fuel loadings are highly variable, particularly in forested systems with an understory component [63][64][65].…”
Section: Fuel Density/consumption Estimatessupporting
confidence: 72%
“…Personal communication, John Maitland, Chief, Forestry Branch, USAG Ft. Jackson to David Weise, 2015. While Fire 2022, 5, 118 sparkleberry was the focus of the present study, Wenk et al [58] found similar results in another prescribed fire study in the Carolina sandhills in longleaf stands where turkey oak (Quercus laevis) was the dominant understory woody plant [59][60][61][62]. It is well-established that natural fuel loadings are highly variable, particularly in forested systems with an understory component [63][64][65].…”
Section: Fuel Density/consumption Estimatessupporting
confidence: 72%
“…These correlations can then be used to derive coefficients for models through regression analysis. This approach has been successfully applied in studies of chaparral crown fires, thus demonstrating the applicability of semi-empirical models in diverse fire scenarios [34]. The plot depicts the dynamics of v, thereby highlighting its behavior over the adjusted time and space range.…”
Section: Profiles Of Analytical Solutionsmentioning
confidence: 92%
“…The data inside the threshold contour takes the value one and the data outside the threshold contour takes the value zero. Following [37], an ellipse is fitted to the binary image at every time level using the MATLAB function regionprops. The ellipse is constrained so that the second moment of the ellipse is equal to the second moment of the nonzero region of the image.…”
Section: Determination Of Flame Lengthmentioning
confidence: 99%